Evaluation of Knowledge and Competence of Kazakhstani Athletes about Nutrition - Yeldana Yerzhanova; Zhanna Sabyrbek; Ermek Dilmakhanbetov; Galiya Madiyeva; Kazys Milasius (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2019)
Knowledge and competences are important for every person, especially they are important for physically active people. Although the knowledge and competence of athletes about nutrition is investigated, this subject is still a relatively new area in the science of nutrition of Kazakhstan athletes. Knowledge and competence is characterized as the ability of an individual to obtain, process and understand basic information on nutrition. The purpose of the work is to determine the level of knowledge, sources and the method of their acquisition by the investigated athletes. 199 students from Al-Farabi Kazakh National University and Abay Kazakh National Pedagogical University were enrolled in 1-4 courses in physical education and sports and 60 athletes of high sportsmanship - 15 volleyball players of Burevestnik teams, 15 judo wrestlers of the Kazakhstan national team, 15 wrestlers of the club team and 15 triathletes of the Kazakhstan national team were engaged in the study of the level of knowledge, method of acquisition of information on nutrition. The questionnaire prepared by Steptoe et al., (1995) was applied during the survey of students, directly interviewing each respondent. Kazakhstani athletes get basic information on nutrition from trainers and family members, and too few are accounted for by doctors and nutritionists. Public information systems are relatively ineffective. A survey of students showed that 26.2% of women and 43.3% of men receive information on nutrition from their trainer and teacher. They do not receive enough information on nutrition from media, radio and television. However, 26.2% of women and 18.5% of men receive such information via the Internet. When regulating body weight, women are mainly guided by their opinions, while men prefer coach recommendations.